Possibilities of homogenization of the kerf width created by the technology of abrasive water-jet cutting - R. Kminiak; Š. Barcík (Journal of Forest Science, 2011)
The paper deals with the possibilities of homogenization of the kerf width by proper choice of the respective feed rate and abrasive mass flow for particular models of cutting. The introductory part is devoted to reasons for the kerf width variability in dependence on the models of cutting, as well as to the methods of determining the kerf width in cutting of solid wood by abrasive water jet. In the conclusion are presented the results concerning the development of kerf width in the range of commonly used feed rates and abrasive mass flows.